2017
DOI: 10.1161/jaha.117.006680
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl 4‐Hydroxylase Domain Protein 3 Overexpression Improved Obstructive Sleep Apnea—Induced Cardiac Perivascular Fibrosis Partially by Suppressing Endothelial‐to‐Mesenchymal Transition

Abstract: BackgroundIntermittent hypoxia (IH) induced by obstructive sleep apnea is the key factor involved in cardiovascular fibrosis. Under persistent hypoxia condition, endothelial cells respond by endothelial‐to‐mesenchymal transition (EndMT), which is associated with cardiovascular fibrosis. Prolyl 4‐hydroxylase domain protein 3 (PHD3) is a cellular oxygen sensor and its expression increased in hypoxia. However, its role in obstructive sleep apnea–induced EndMT and cardiovascular fibrosis is still uncertain. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The obvious modifications in cardiovascular remodelling are characterized by the disruption of normal myocardial structure through excessive collagen deposition. Our previous study confirms that OSA can induce cardiac perivascular fibrosis [12]. However, the detailed mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…The obvious modifications in cardiovascular remodelling are characterized by the disruption of normal myocardial structure through excessive collagen deposition. Our previous study confirms that OSA can induce cardiac perivascular fibrosis [12]. However, the detailed mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 53%
“…Our previous study had shown that IH can induce PHD3 expression in vitro and vivo [12]. To ascertain whether PHD3 could improve cardiac fibrosis induced by IH, in this study, lentivirus was applied to intervene the expression of PHD3 in vivo and vitro.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations